The Effect of Inside Outside Circle And Numbered Heads Together Methods on High and Low Interest Students Reading Comprehension (A case at 8th grade in NU Islamic High School of Ungaran Barat in the Academic Year of 2014/2015) - Ida Ubaidah Hidayati (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The aims of this research were to improve (1) to explain the effect of Inside-Outside Circle (IOC) on high interest students at grade 8th of Islamic High School NU Ungaran Barat, (2) to explain the effect Inside-Outside Circle (IOC) technique on low interest students at grade 8th of Islamic high School NU Ungaran Barat, (3) to explain Numbered Heads together (NHT) on high interest students at grade 8th of Islamic High School NU Ungaran Barat (4) to explain Numbered Heads together (NHT) on low interest students at grade 8th of Islamic High School NU Ungaran Barat(5) to explain the significant of the interaction among technique, reading comprehension, and Students interest at grade 8th of Islamic High School NU Ungaran Barat. This research was a quantitative research, using an experimental study. The participants of this study were 64 students of Islamic High School of Ungaran Barat. The students were devided into two groups, they are; control group and experimental group. The result shows that numbered heads Together has more effect to teach reading comprehension that Inside outside circle with the significant different of 0,05 ? 0.042 and the NHT (Numbered Heads Together) mean score was 78.250 while IOC (Inside outside circle) 80.156 for high interest. The difference between the means for high and low students was 1.90 while for low interest, the technique of IOC (inside outside circle) was more implemented. It was showed from the data it increased students readin comprehension from them who were in low grade.